Rancang Bangun Aplikasi Android Si-Raja sebagai Upaya Memantau Pertumbuhan Janin pada Ibu Hamil : Designing the Si-Raja Android Application as an Effort to Monitor Fetal Growth in Pregnant Women - Darwitri, Darwitri; Harianja, Ristina Rosauli; Sihaloho, Metasari; Batubara, Kartika Sri Dewi (Poltekes Kemenkes Tanjungpinang, 2023)
Pregnancy is fertilization or union of spermatozoa and ovum, followed by nidation or implantation. Determining estimated fetal weight (TBJ) is vital in antenatal care, counseling, diagnosis and delivery approaches. Accurate predictions of a baby's birth weight are one of the most crucial metrics in pregnancy until the commencement of labor. The health application for pregnant women has been produced in prototype form that may be run on the Android smartphone operating system. Pregnant women used the application. Apart from that, the Si-RAJA Pregnant Application was a development of the Si-RAJA application version 1. This application was built so that pregnant ladies can use it to find out the estimated weight of their fetus. This program was provided with functions to compute weight gain, upper arm circumference, and hemoglobin level status, as well as health information about fetal growth that pregnant women need to know. One of the prerequisites that needed to be met before beginning the application was to install it on your smartphone via Google Playstore. The Si-Raja Bumil program comprises of the primary menu: Calculate predicted fetal weight, how to enhance TBJ, Calculate upper arm circumference, calculate weight gain, calculate Hb levels, as well as information about the size of the baby. The program is expected to go through significant enhancements, enabling pregnant women to effectively engage with midwives to transmit complaints, examination findings, and pregnancy-related information.